Antibodies to the Caspr1/contactin-1 complex in chronic inflammatory demyelinating polyradiculoneuropathy - Pascual-Goñi, Elba; Fehmi, Janev; Lleixà, Cinta; Martín-Aguilar, Lorena; Devaux, Jérôme; Höftberger, Romana; Delmont, Emilien; Doppler, Kathrin; Sommer, Claudia; Radunovic, Aleksandar; Carvajal, Alejandra; Smyth, Shane; et al. (Brain (London, England : 1878), 2021)
Previous studies have described the clinical, serological and pathological features of patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and antibodies directed against the paranodal proteins neurofascin-155, contactin-1 (CNTN1), contactin-associated protein-1 (Caspr1), or nodal forms of neurofascin. Such antibodies are useful for diagnosis and potentially treatment selection. However, antibodies targeting Caspr1 only or the Caspr1/CNTN1 complex have been reported in few patients with CIDP. Moreover, it is unclear if these patients belong to the same pathophysiological subgroup. Using cell-based assays in routine clinical testing, we identified sera from patients with CIDP showing strong membrane reactivity when both CNTN1 and Caspr1 were co-transfected (but not when CNTN1 was transfected alone). Fifteen patients (10 male; aged between 40 and 75) with antibodies targeting Caspr1/CNTN1 co-transfected cells were enrolled for characterization. The prevalence of anti-Caspr1/CNTN1 antibodies was 1.9% (1/52) in the Sant Pau CIDP cohort, and 4.3% (1/23) in a German cohort of acute-onset CIDP. All patients fulfilled European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) definite diagnostic criteria for CIDP. Seven (47%) were initially diagnosed with Guillain-Barré syndrome due to an acute-subacute onset. Six (40%) patients had cranial nerve involvement, eight (53%) reported neuropathic pain and 12 (80%) ataxia. Axonal involvement and acute denervation were frequent in electrophysiological studies. Complete response to intravenous immunoglobulin was not observed, while most (90%) responded well to rituximab. Enzyme-linked immunosorbent assay (ELISA) and teased nerve fibre immunohistochemistry confirmed reactivity against the paranodal Caspr1/CNTN1 complex. Weaker reactivity against Caspr1 transfected alone was also detected in 10/15 (67%). Sera from 13 of these patients were available for testing by ELISA. All 13 samples reacted against Caspr1 by ELISA and this reactivity was enhanced when CNTN1 was added to the Caspr1 ELISA. IgG subclasses were also investigated by ELISA. IgG4 was the predominant subclass in 10 patients, while IgG3 was predominant in other three patients. In conclusion, patients with antibodies to the Caspr1/CNTN1 complex display similar serological and clinical features and constitute a single subgroup within the CIDP syndrome. These antibodies likely target Caspr1 primarily and are detected with Caspr1-only ELISA, but reactivity is optimal when CNTN1 is added to Caspr1 in cell-based assays and ELISA.